Cerebrolysin: spectrum of activity and research data. Part 2 - N. D. Bukreeva; E. A. Rakityanskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The results of analysis of experimental and clinical studies have shown that Cerebrolysin application is safe and effective therapy for many neurological disorders ranging from stroke and ending Alzheimer’s disease. The primary effect of the medicine is associated with the influence of Cerebrolysin on certain areas of the hippocampus and their function. The medicine has a unique organ-multimodal action on the brain, it is capable of metabolic regulation, neuroprotection, functional neuromodulation and neurotrophic activity, detected in numerous experimental studies. The clinical efficacy of the medicine is confirmed by clinical trials performed based on GCP requirements.